Antibody profiles induced by Trypanosoma cruzi in chagasic patients with previous or current exposure to mycobacteria - Peverengo, Luz; Prochetto, Estefanía; Rodeles, Luz; Valenzuela, Ignacio; Marcipar, Iván Sergio; Bottasso, Oscar; Vicco, Miguel Hernán (Pathogens and disease, 2016)
Since the immune response mounted by the host to a particular microorganism might be influenced by the acquired immunological experience due to previous contact with other microorganisms, we performed a cross-sectional study to explore the pattern of Trypanosoma cruzi infection-related antibodies in T. cruzi-seropositive individuals presenting concomitant tuberculosis, or the antecedent of BCG vaccination. Sampled individuals were grouped as follows: patients with Chagas disease, not vaccinated with BCG, who further developed pulmonary tuberculosis; individuals with Chagas disease, BCG-vaccinated; and subjects with Chagas disease, presenting neither BCG scar nor tuberculosis disease. Non-vaccinated individuals or without tuberculosis, presented the highest values of anti-PH (P < 0.001), anti-FRA (P < 0.001), anti-p2β (P = 0.0023) and anti-B13 (P < 0.001) antibodies. The present findings constitute the first demonstration of the potential influence of concomitant tuberculosis on Chagas disease.